Clinical characteristics and analysis of cerebrospinal fluid biochemical, tumor markers and cytologic indices in 209 patients with meningeal carcinomatosis: a cross-sectional study - Xu, Shaoqiang; Huang, Chunxia; Ye, Yuanyang; Lai, Keyuan; Lan, Sihan; Chen, Jinhao (Frontiers in Oncology, 2025)
ObjectiveTo analyze the clinical characteristics and cerebrospinal fluid (CSF) biochemical indexes, tumor markers (TM) and cytomorphological indexes of patients with meningeal carcinomatosis (MC), and to explore the clinical application value of the above indexes.MethodsRetrospectively included 209 patients with MC in 2021–2023 into the study and collected their clinical information and laboratory data, compared the differences in indicators and analyzed the cytomorphological features and dynamic changes.Results(i) The primary foci of MC patients were mostly lung cancer (86.6%), and the clinical manifestations did not change according to the tumor of the primary foci. The main manifestations were headache (65.55%) and meningeal enhancement (67.20%); (ii)Most MC patients (96.17%) had abnormal CSF biochemical indices, with some variations among primary foci; (iii) CYFRA21–1 level in CSF of MC patients was significantly higher than that in serum (P<0.05); (iv) The first detection rate of atypical cells in CSF of MC patients in our center was 95.22%, and the morphological characteristics were correlated with the primary foci; (v)Dynamic monitoring showed that the level of TM in CSF was consistent with the changes in the proportion of atypical cells in CSF, which could suggest fluctuations in the disease.ConclusionIn this study, it is clear that the clinical characteristics of MC patients and the CSF indicators have specific distribution patterns, and the combined analysis of CSF biochemical indicators, TMr levels and cytomorphology can provide a key basis for the diagnosis of MC, the indication of primary foci and the monitoring of the disease, and the large-scale single-center data provide a reliable support for its clinical application.